KONTRUKSI KONSEP CATUR LAWA PURA DASAR BHUWANA GELGEL KLUNGKUNG - Anak Agung Gde Raka; I Made Suwitra; Anak Agung Gede Raka Gunawarman (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
The multi-concept underlies the establishment of the Bhuwana Gelgel Klungkung Temple. Therefore, knowledge of the concepts that are applied is needed so that they are not mistaken in understanding the form, function, and status of the temple. When observing the object, it appears that there are certain groups who think that the two pelinggih (temples) with Catur Lawa status, namely Meru Tumpang Tiga Pelinggih Ratu Pasek and Meru Tumpang Tiga Pelinggih Ratu Pande, are pelinggih for the worship of their ancestral spirits. In order to avoid continuous misunderstandings, in this study, the construction of the concept was carried out and returned to its essence. The research which carries the title "Construction of the Concept of Catur Lawa Pura Basis Bhuwana Gelgel Klungkung" uses a qualitative approach. In collecting the data, the methods of observation, interviews, and literature study were used.